ASRAMA MAHASISWA UNTAR DENGAN PENERAPAN RUANG KOMUNAL - Hendrik Heriyanto; Sutarki Sutisna (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
Student dormitories have an important role in providing a comfortable place to live and support their social development. However, dormitories often only focus on physical aspects, such as providing sleeping space and basic facilities, without paying attention to the social needs of students. In this context, implementing empathetic communal spaces is a relevant solution. By implementing empathetic communal spaces, dormitories provide attention and respect for students as individuals in a dormitory environment. This communal space is designed to support students' social development, allowing them to share experiences, ideas and creativity. This approach is based on empathic architecture, which aims to create an environment that pays attention to and cares for the social needs of students. The application of communal space in student dormitory designs as a solution to empathic architecture makes a positive contribution in creating an environment that pays attention to students' social needs. This not only promotes healthy social interaction between students, but also enhances their experience of living during their studies in the hostel. With an empathic communal space, students can feel supported, valued and cared for as individuals, which in turn can help in their social development. In conclusion, the application of communal space in student dormitory design as a solution to empathic architecture has a positive impact on creating an environment that pays attention to the social needs of students. This creates a space for healthy social interaction and enhances their life experience during their study period at the hostel. Keywords: empathy architecture; student dormitory; communal space Abstrak Asrama mahasiswa memiliki peran penting dalam menyediakan tempat tinggal yang nyaman dan mendukung perkembangan sosial mereka. Namun, seringkali asrama hanya fokus pada aspek fisik semata, seperti menyediakan ruang tidur dan fasilitas dasar, tanpa memperhatikan kebutuhan sosial mahasiswa. Dalam konteks ini, penerapan ruang komunal yang empatik menjadi solusi yang relevan.Dengan menerapkan ruang komunal yang empatik, asrama memberikan perhatian dan penghargaan terhadap mahasiswa sebagai individu dalam lingkungan asrama. Ruang komunal ini dirancang untuk mendukung perkembangan sosial mahasiswa, memungkinkan mereka berbagi pengalaman, ide, dan kreativitas. Pendekatan ini didasarkan pada arsitektur empatik, yang bertujuan menciptakan lingkungan yang memperhatikan dan peduli terhadap kebutuhan sosial mahasiswa.Penerapan ruang komunal dalam desain dormitory mahasiswa sebagai solusi dari arsitektur empatik memberikan kontribusi positif dalam menciptakan lingkungan yang memperhatikan kebutuhan sosial mahasiswa. Ini tidak hanya mempromosikan interaksi sosial yang sehat antara mahasiswa, tetapi juga meningkatkan pengalaman hidup mereka selama masa studi di asrama. Dengan adanya ruang komunal yang empatik, mahasiswa dapat merasa didukung, dihargai, dan diperhatikan sebagai individu, yang pada gilirannya dapat membantu dalam perkembangan sosial mereka. Penerapan ruang komunal dalam desain dormitory mahasiswa sebagai solusi dari arsitektur empatik memberikan dampak positif dalam menciptakan lingkungan asrama yang memperhatikan kebutuhan sosial mahasiswa. Ini menciptakan ruang untuk interaksi sosial yang sehat dan meningkatkan pengalaman hidup mereka selama masa studi di asrama.